The quality of the spatial environment of patient room in the hospitalsCase study: Specialist surgical building at Al- Shifa hospital in the Gaza- Palestine: جودة البيئة المكانية لفراغات غرف المرضى بالمستشفيات حالة دراسية: مبنى الجراحات التخصصية بمجمع الشفاء الطبي في غزة- فلسطين - Nagham Khader Ali Hassan, Mohamed Mohamed Abed Rabbo Almogir (Journal of engineering sciences and information technology, 2018)
The study aimed at assessing the quality of the indoor spaces in one of the buildings of Shifa hospital, as a case study, through the assessment of psychological comfort, Environmental interference and management to improve the quality of the spatial environment of patient room in the Gaza Strip hospitals. The research study adopted the analytical descriptive approach to the existing situation of patients rooms in the upper floors of the building through field visits and interviews of patients, administrative and nursing staff. Thus analyzing the data and results obtained from the questionnaire for spatial environmental management. The study set recommendations that will improve the spatial environment in hospital.